Evaluation Of Overweight Loads On Freight Transportation In Relation To Road Damage And Safety - Ipana Novela; Imam Basuki (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2025)
Basically, the structural function of the road will decrease over time, especially when the road is often passed by overloaded vehicles. The decline in road structural function will affect road user comfort, road user safety, transportation efficiency, accessibility, environment and other factors.The results of the study showed that of the total road length of 30,7 km with a road width of 7 m, about 6.52 km were damaged caused by overloading vehicles. The overall level of damage is categorized as lightly damaged based on the Bina Marga and SDI methods, although there are several segments that are in a severely damaged condition. The percentage of road damage caused by overloading vehicles was 14,563.35 m² (6.50%). The dominant types of damage include holes (3.01%), sinks (1.43%), and waves/curls (0.81%).The implementation of regulations on ODOL vehicles, regular road maintenance, and driver education are needed to improve safety, reduce the risk of accidents, and maintain the comfort of road users.